Incorporating Microblogging (“Tweeting”) in Higher Education: Lessons Learnt in a Knowledge Management Course - Menkhoff, Thomas (Institutional Knowledge at Singapore Management University, 2015)
This paper features a competency-enhancing social networking application which provides a solution for the dilemma of non-participating (non-engaged) students in class: ‘pedagogical tweeting’. Twitter’s micro-blogging service enables both instructors and students to send and read messages (tweets) of up to 140 characters, incl. links to blogs, web pages, photos, videos, etc. As Twitter can be accessed from a website, via applications on PC/Mac, iPhone, Android phones, etc., it represents an effective tool to engage students, e.g. by taking up questions during in-class and out-of-class discussions or by providing advice on assignments etc. Students in turn can generate their own learning context and benefit from collaborative knowledge creation. We share respective tweeting experiences made during a course on Knowledge Management (KM) taught at Singapore Management University (SMU) backed up by exploratory research on students’ micro-blogging activities. We discuss challenges ahead and propose four hypotheses about the effective deployment of social awareness streams such as Twitter in higher education.